39. Hålogalandsvegen gjennom 10 000 år: Resultater og potensiale - Jørgensen, Erlend Kirkeng; Bruun, Inga Malene; Oppvang, Janne (Tromura, 2025)
Synthesis of the project with a focus on results and research potential. The synthesis highlights resource utilization, mobility, settlement patterns, and tool use. The chapter summarizes the findings from the reports on the various sites and examines these in relation to the project’s research questions.